2020
DOI: 10.21203/rs.3.rs-22046/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The primary total knee arthroplasty: a global analysis

Abstract: Background The use of total knee arthroplasty (TKA) in treatment of chronic degenerative pathologies of the knee has boasted of an experience of 50 years. The aim of this bibliometric and visualized study is to comprehensively examine the current status and global trends of TKA research. Methods Publications related to TKA research from 2010 to 2019 were retrieved from Web of Science database, and then analyzed through bibliometric methodology. As for the visualized study, the software VOS viewer was utiliz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…On the basis of the number of publications with cooccurrence, cooccurrence analysis was performed to assess the relationship between the identified items. In addition, it is thought to be an effective method for predicting future trends and hotspots in research areas of interest [ 26 ]. In the present study, we showed a network graph of the cooccurrence relationship by analyzing the keywords of all the included research.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the number of publications with cooccurrence, cooccurrence analysis was performed to assess the relationship between the identified items. In addition, it is thought to be an effective method for predicting future trends and hotspots in research areas of interest [ 26 ]. In the present study, we showed a network graph of the cooccurrence relationship by analyzing the keywords of all the included research.…”
Section: Discussionmentioning
confidence: 99%
“…This combination plotted the map of twenty-seven thresholds out of four thousand nine hundred and fifty-two authors, in eight clusters. [1][2][3] thedensity visualization map of co-authorship analysis plotted in figure 2, points out the major researchers with their strong coauthorship linkages. [4][5] The major clusters involved in the research with co-authorship can be identified in figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Even though these huge numbers should be connected with high satisfaction among patients, about 20% of them are unsatisfied with the outcome of the surgery while the average satisfaction after another arthroplasty procedure, hip replacement rate reaches 93% [ [5] , [6] , [7] ]. Looking for the reason for such differences, there is an ongoing debate over the best implant design, its positioning, surgical technique, alignment, and perioperative care [ [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%